Mechanistic insights into the pathogenesis and management of acute pancreatitis - Haidy E Michel; Naglaa Gamal; Mariane G Tadros (Ain Shams University, 2022)
Acute pancreatitis (AP) is an inflammatory disorder of the pancreas; its incidence rate is increasing worldwide; it is around 34 cases per 100,000 persons/year. It may range from mild to severe cases and may be associated with morbidity and mortality mainly due to multiple organ dysfunction syndrome (MODS). Till now, there is no specific therapy for the disease and the treatment of AP is mainly supportive, also the underlying mechanisms included in its pathogenesis are not fully clear. However, it may include oxidative stress and inflammatory response, including critical mediators, such as interleukin-1β (IL-1β), tumor necrosis factor- α (TNF-α), toll like receptor-4 (TLR-4), nuclear factor-kappa B (NF-κB), and high-mobility group box protein1 (HMGB1). Thus, there is a pressing need for continuous search in this era to clarify different pathogenesis and the development of new treatment options for AP, also understanding of the disease. While research on the human pancreas remains challenging, animal models of AP may help to elucidate the disease pathophysiology & to discover new target options for the development of new therapies. This review aims to revise several aspects related to AP diagnosis and management and to summarize different animal models of AP.